Mechanical, anti-bacterial, and easy-to-clean properties of hybrid polymer-based composites containing modified SiO2 prepared by thermal polymerization - Kesmez, Omer; Arpac, Ertugrul; Kiraz, Nadir; Selli, Neslihan Tamsu; Tunali, Ayse (Springer International Publishing Ag, 2020)
The advance in modern technology brings about the needs arising in the field of materials. In this study, thermal behavior, mechanical properties, composite morphology, anti-bacterial efficiency, and easy-to-clean properties of the hybrid composite polymers consisting of 2-hydroxyethyl methacrylate-diurethane dimethacrylate (HEMA-DUDMA) as an organic polymer and 3-(trimethoxysilyl)propyl methacrylate-modified SiO2 used as a reinforcement were investigated. Organic polymers were prepared by free radical polymerization via thermal methods. For this purpose, HEMA was used as the monofunctional methacrylate and ethylene glycol dimethacrylate; triethylene glycol dimethacrylate and DUDMA were used as the difunctional methacrylate compounds. The modified SiO2 ceramic particles were added into the optimum organic polymer, and it was provided anti-bacterial and easy-to-clean properties for the obtained hybrid polymer composites. The conclusion reached a high hardness value, thermally stable, anti-bacterial, and easy-to-clean properties. It may be suggested that the obtained hybrid polymer composites are suitable for the potential commercial area application. [GRAPHICS] .
Keywords: Polymer composites; Cross-linking; Radical polymerization; Thermal properties; Hybrid; SiO2